Trends antimicrobial resistance in urinary tract infections: a research at the Dr. Zainoel Abidin Teaching Hospital, Banda Aceh, Indonesia - Said A. Khalilullah; Devi Susanti; Ramadhan W. Saputra; . Nurjannah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The aim of this study was to identify the most common bacterial cause of urinary tract infections and the patterns of antimicrobial resistance. The study was conducted at Dr. Zainoel Abidin Teaching Hospital, Banda Aceh, Indonesia with descriptive retrospective study approach.  The data was taken from medical records. One hundred and nineteen bacterials was identified, encountered gram-negative bacteria namely Escherichia coli (31.7%), Klebsiella pneumoniae (27.7%), Acinetobacter (12.6%), Pseudomonas aeruginosa (10.1%), Enterobacter (5.1%) and Proteus mirabilis (0.8%). Meanwhile encountered gram-positive bacteria were Beta-hemolytic Streptococci (9.2%) and Staphylococcus aureus (3.4%). Observations on the sensitivity profile suggested that the pathogenic gram-negative bacteria had a high resistance against ampicilin, ciprofloxacin, cefuroxime and cefotaxime, while meropenem, chloramphenicol, gentamicin and tobramycin have a high sensitivity level. Descriptive analysis also found pathogenic gram-positive bacteria showed high resistance to ceftriaxone, clindamycin, tetracycline and cephalotin and had a high sensitivity level to meropenem, vancomycin and oxacillin. Based on these results we concluded that the most common of urinary tract infections were caused by gram-negative bacteria species Escherichia coli. Encounters a high resistance pattern to 3rd generation cephalosporin antibiotics group, this was caused by the irrational use of antibiotics and the ability of bacteria to produce beta-lactamase enzymes which results in degradation of beta-lactam ring (β-lactam). We recommended the antibiotics group of chloramphenicol, gentamicin and vancomycin to use as empirical therapy in urinary tract infections. Antibiotic treatment should be prescribed only for as long as necessary to be effective. Recurrent urinary tract infections may be managed better by self initiated therapy or prophylaxis than by continuing to treat each case emergently. We also recommend health practitioners to use antibiotics rationally to prevent the resistances.